ANALISIS UPAYA-UPAYA PENURUNAN BERAT BADAN PADA MAHASISWI ANGKATAN 2010 FAKULTAS KEDOKTERAN UNIVERSITAS SAM RATULANGI MANADO - Nussy, Christine Yelika; Ratag, Gustaaf A. E.; Mayulu, Nelly (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2014)
Obesity is an overweight condition caused by the accumulation of fat, in both men and women, which has to be more than20-25% of their bodyweight. According to a national baseline health research (Riset Kesehatan Dasar [Riskesdas]) in2007, prevalent rate on the population above age of 15 has reached 10,3% (males 13,9%, females 23,8%). The purpose ofthis research is to analyze the efforts to decrease body weight in the female students of the Medical Faculty of Sam RatulangiUniversity Manado. The qualitative method was used in this research and this was held at Medical Faculty of SamRatulangi University Manado on November 2013 to January 2014. The informants were chosen by using purposive samplingmethod and it had been decided that 10 informants would be interviewed. The collected data would be analyzedthen validated using triangulation sources and method. The female medical school students of Sam Ratulangi UniversityManado in year 2010 realized the risk of obesity and took precautions to decrease their weight by done physical training,consumed lower calorie foods, and held their hunger. There were some obstacles, such as lack of time to do physical activities,laziness and wrong diet program.Keywords: Obesity, College Student, effort to decrease body weight